Stimulation of Nicotinamide Adenine Dinucleotide Biosynthetic Pathways Delays Axonal Degeneration after Axotomy - Sasaki, Yo (J Neurosci, 2006)
Axonal degeneration occurs in many neurodegenerative diseases and after traumatic injury and is a self-destructive program independent from programmed cell death. Previous studies demonstrated that overexpression of nicotinamide mononucleotide adenylyltransferase 1 (Nmnat1) or exogenous application of nicotinamide adenine dinucleotide (NAD) can protect axons of cultured dorsal root ganglion (DRG) neurons from degeneration caused by mechanical or neurotoxic injury. In mammalian cells, NAD can be synthesized from multiple precursors, including tryptophan, nicotinic acid, nicotinamide, and nicotinamide riboside (NmR), via multiple enzymatic steps. To determine whether other components of these NAD biosynthetic pathways are capable of delaying axonal degeneration, we overexpressed each of the enzymes involved in each pathway and/or exogenously administered their respective substrates in DRG cultures and assessed their capacity to protect axons after axotomy. Among the enzymes tested, Nmnat1 had the strongest protective effects, whereas nicotinamide phosphoribosyl transferase and nicotinic acid phosphoribosyl transferase showed moderate protective activity in the presence of their substrates. Strong axonal protection was also provided by Nmnat3, which is predominantly located in mitochondria, and an Nmnat1 mutant localized to the cytoplasm, indicating that the subcellular location of NAD production is not crucial for protective activity. In addition, we showed that exogenous application of the NAD precursors that are the substrates of these enzymes, including nicotinic acid mononucleotide, nicotinamide mononucleotide, and NmR, can also delay axonal degeneration. These results indicate that stimulation of NAD biosynthetic pathways via a variety of interventions may be useful in preventing or delaying axonal degeneration.